Effect of high-protein milk on lipid profiles and blood glucose in young adult - Harna Harna; Clara Meliyanti Kusharto; Katrin Roosita; Andi Muh Asrul Irawan; Mertien Sa’pang; Prita Dhyani Swamilaksita (Jurnal Gizi Klinik Indonesia, 2022)
Background: High-protein milk is a complex food that contains several potentially bioactive compounds that might affect blood glucose and cholesterol. Epidemiological data indicate that high-protein milk consumption is associated with a decrease in the prevalence of metabolic disorders or maintaining metabolic health.Objective: This study aimed to analyze the effect of high-protein milk on cholesterol, low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglycerides, and fasting blood glucose.Methods: This study used an experimental trial with the designed randomized controlled trial. The subjects were divided into two groups: 24 subjects in the treatment group and 23 subjects in the control group. The treatment group was given high-protein milk and nutritional education for 90 days. The control groups were given nutritional education.Results: The results showed that blood glucose did not have a significant difference between the two groups (p>0.05), but it decreased 1.75±3.6 mg/dl after high-protein milk intervention. Blood cholesterol and LDL showed significant differences between the two groups (p<0.05). HDL and triglycerides showed no significant difference between the two groups (p>0.05).Conclusion: Intervention of high-protein milk could significantly reduce cholesterol and LDL levels and reduce blood glucose after 90 days of intervention in the young adult age group. High-protein milk can be a recommendation to prevent metabolic syndrome.